Parental Perception of Using Stories in Developing Children’s English Language Literacy - Mahayani, Putu Angelia Putri; Ratminingsih, Ni Made; Santosa, Made Hery (STKIP AGAMA HINDU SINGARAJA, 2025)
This study explored parental perceptions of their involvement in supporting children's English literacy in grades 4th, 5th, and 6th by using stories as reading media at home. Using an explanatory sequential mixed-method approach, this study involved parents from two junior high schools in Buleleng, Bali. The data were analyzed descriptively using the PAIT (Psychometric Analysis of Item Theory) and CTT (Classical Test Theory) methods, which focused on the reliability and validity of the questionnaire. The results showed that parents had positive perceptions of their engagement in developing children's literacy at home. The cognitive engagement aspect showed a very positive perception, while the behavioral engagement and emotional engagement aspects were classified in the positive category. These findings highlight the need for literacy strategies that not only improve reading skills, but also strengthen children's emotional bonds. Educators need to support parents in balancing academic expectations which fostering children’s love of reading. In addition, policies should promote literacy as a shared responsibility between schools and families, with programs that equip parents as literacy role models from an early age.